The friendship code - Deutsch, Stacia (Girls who code, 2017)
Looking forward to joining the new coding club at school so that she can develop her app idea, Lucy is disappointed by the lukewarm reception she receives from the club's other members, who work with her to decipher mysterious coding notes.